Comparison of growth performances in mixed-sex populations of Oreochromis niloticus (Linnaeus, 1758) from the wild brood’s tock collected from the mono, Niger, ouémé watershed and from a fish farm in Benin - Fagbemi, Mohammed; Aïzonou, Romaric; Agbohessou, Pamphile; Lederoun, Djiman; Agadjihouede, Hyppolyte; LALEYE, PHILIPPE A. (My University, 2019)
In order to evaluate the growth performance of various Oreochromis niloticus populations and identify the best performing one mixed-sex production, a study was conducted on populations collected from three river basins (the Mono, Niger, and Ouémé watershed)as well as from the Yohan-Estève fish farm (2 populations) in Benin. Juveniles were produced at the research station at University of Abomey-Calavi from May to August 2017 and growth tests were conducted from September to November 2017. A duplicate of 30 individuals, with an initial mean body weight of 6.70±1.46 g per population, was set up for each of the seven populations and loaded into square basins (0.99 x 0.99 x 1 m) in which the water depth was maintained at 50cm. The fish were fed for 60 days with extruded BIOMAR fish feed (49% protein and 12% lipid) with a daily diet continuously adjusted to their biomass throughout the experimentation. At the end of the experiment, the survival rate was 100% and the final mean body weight ranged from 18.9 ± 5.9g to 40.9 ± 14.5 g. The maximum final mean body weight was 40.9 ± 14.5 g for the Sohoumè population in the Mono watershed while the lowest was 18.93±5.87 g for the Djonougoui population within the same watershed. The specific growth rate ranged from 1.7 to 3%/day, the feed conversion ratio ranged from 1.2 to 2.3 g/g, and feed efficiency ranged from 42.8 to 81.9%. The basis of the results, it appears that the Sohoumé population displays the best growth performances for a mixed-sex production of O. niloticus.
Keywords: Nile tilapia; mono; ouémé; Niger; fish populations; fish growth performances